Mixed convection characteristic in a lid-driven cavity containing heated triangular block: Effect of location and size of block - Gangawane, Krunal M.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
The present work examines the influence of location of the heated triangular block along the vertical centerline of cavity on mixed convection characteristics. The flow is assumed to be 2D, steady, laminar and for incompressible and Newtonian. The physical domain of study is top lid-driven square cavity. The top and bottom walls of cavity are thermally insulated; while the both vertical walls are exposed to ambient (T-c). The cavity contains equilateral triangular block (size of edge, b), maintained at isothermal temperature condition (T-H(> T-c)) along its geometric horizontal centerline. The change in the position of block is permitted along the vertical centerline (x = 0.5,y) of cavity. Flow pertaining equations are solved by using finite volume method (FVM) and SIMPLE algorithm. The dependence of various relevant dimensionless parameter, such as, Reynolds number (Re = 1-1000), Richardson number (Ri = 0.01, 1, 10), blockage ((B) over bar = 0.1, 0.2, 0.3) and location (L-y = 0.25, 0.5, 0.75) of triangular block on convection characteristics have been elucidated. Flow and thermal patterns in the cavity are analyzed by systematic evaluation of streamline and temperature contours. Followed by heat transfer characteristics are presented by studying variation of local as well as average Nusselt number. Average Nu values are presented in the form of tables for different values of Ri. Higher heat transfer rates can be achieved for centered block position (L-y = 0.5) than remaining two (L-y = 0.25, 0.75). (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Triangular block; Lid-driven cavity; Richardson number; Nusselt number; Reynolds number; Finite volume method